Individualized Pharmacological Treatment of Neuropathic Pain. Issue 2 (15th December 2014) - Helfert, SM; Reimer, M; Höper, J; Baron, R
<x xml:space="preserve">Abstract</x> Patients with the same disease may suffer from completely different pain symptoms yet receive the same drug treatment. Several studies elucidate neuropathic pain and treatment response in human surrogate pain models. They show promising results toward a patient stratification according to the mechanisms underlying the pain, as reflected in their symptoms. Several promising new drugs produced negative study results in clinical phase III trials. However, retrospective analysis of treatment response based on baseline pain phenotyping could demonstrate positive results for certain subgroups of patients. Thus, a prospective classification of patients according to pain phenotype may play an increasingly important role in personalized treatment of neuropathic pain states. A recent prospective study using stratification based on pain‐related sensory abnormalities confirmed the concept of personalized pharmacological treatment of neuropathic pain.